If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7v + 3)(7v + 9) = 0 Reorder the terms: (3 + 7v)(7v + 9) = 0 Reorder the terms: (3 + 7v)(9 + 7v) = 0 Multiply (3 + 7v) * (9 + 7v) (3(9 + 7v) + 7v * (9 + 7v)) = 0 ((9 * 3 + 7v * 3) + 7v * (9 + 7v)) = 0 ((27 + 21v) + 7v * (9 + 7v)) = 0 (27 + 21v + (9 * 7v + 7v * 7v)) = 0 (27 + 21v + (63v + 49v2)) = 0 Combine like terms: 21v + 63v = 84v (27 + 84v + 49v2) = 0 Solving 27 + 84v + 49v2 = 0 Solving for variable 'v'. Factor a trinomial. (9 + 7v)(3 + 7v) = 0Subproblem 1
Set the factor '(9 + 7v)' equal to zero and attempt to solve: Simplifying 9 + 7v = 0 Solving 9 + 7v = 0 Move all terms containing v to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 7v = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 7v = 0 + -9 7v = 0 + -9 Combine like terms: 0 + -9 = -9 7v = -9 Divide each side by '7'. v = -1.285714286 Simplifying v = -1.285714286Subproblem 2
Set the factor '(3 + 7v)' equal to zero and attempt to solve: Simplifying 3 + 7v = 0 Solving 3 + 7v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 7v = 0 + -3 7v = 0 + -3 Combine like terms: 0 + -3 = -3 7v = -3 Divide each side by '7'. v = -0.4285714286 Simplifying v = -0.4285714286Solution
v = {-1.285714286, -0.4285714286}
| y=-2x^5+16x^4+66x^3 | | z^2-5z+7+z=0 | | 15z^2+7z-16=0 | | g(9g+7)=0 | | 8x+8=38 | | x+8.8=33 | | .80x+.85(40)=.40(75) | | (f-8)(8f-5)=0 | | 7x+3-2x+9-5x=19 | | (1+2i)(1-2i)=0 | | 2.25=-2.67x-1.83x | | 8a+11=3a+41 | | x+7.7=33 | | (r-8)(r+1)=0 | | x-25=-65 | | 6(r-4)=-5r+31 | | y=10x^4-360x^2 | | (k-8)(k+2)=0 | | x^2+bx+c=r | | v+5.5=31.1 | | 4.3t-2.1t-0.2c=7.6 | | 3(4x+7)=9x-3 | | 5z-23=-41+3z | | (z+7)(4z+9)=0 | | 8x-30+6x+84=180 | | 4(3x+2)-3= | | 1.3+v=5.3 | | 5z-23=-41+32 | | 2x^2+2y^2-20x-16y-16=0 | | 2.6x+1.17-3.4=5.2 | | 6+3y-3=7y+5-5y | | 3(6x+2)-18x=12 |